Prediction of Future Temperature and Rainfall Characteristics Using Statistical Downscaling Model (SDSM) for Empangan Sg. Sembrong in Batu Pahat Catchment - LATIFF, NURUL HIDAYAH (Progress in Engineering Application and Technology, 2021)
Climate changes has become major driver to increase of global temperature, precipitation and wind, that sometimes may leads to occurrence of extreme weather. The climate change gives huge impacts to the temperature and rainfall, thus affecting the quantity of water resources at Sembrong dam reservoir.The study aims to calibrate, validate temperature and rainfall simulation; and to project future temperature and rainfall from 2020 to 2050 by using Statistical Downscaling Models (SDSM). The calibration and validation conducted using NCEP output and rainfall or temperature data, while the projection of future temperature and rainfall conducted based on RCPs scenario, which are RCP4.5 and RCP8.5. The observed data and simulated NCEP results are compared to observe the correlation to the local predictand. The projected temperature and rainfall produces the higher increment for scenario of RCP8.5 compare to RCP4.5. The outcomes of this study can be used to provide planning on conservation of water to maintain the availability of water supply.